Tata Kelola Bank Syariah Di Era Digital: Studi Literatur Peran Dewan Pengawas Syariah - Ade Asminaria Sihombing; Evi Syuriani Harahap; Excaudia Mazmuris Siringo-Ringo; Erikson Sinaga; Pintar Rohsangapta Padang (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to systematically examine the role of the Sharia Supervisory Board (DPS) in Islamic bank governance amidst the acceleration of digital transformation. Using a Systematic Literature Review (SLR) methodology, this research analyzes 47 scientific articles published between 2015 and 2024 from Scopus, Web of Science, and Google Scholar databases. The findings reveal that the DPS faces three primary challenges in the digital era: (1) limited digital competency in supervising financial technology (fintech)-based products and services; (2) inadequate regulatory frameworks for blockchain and artificial intelligence (AI)-based transactions; and (3) the potential for deviations from Sharia principles in digital banking operations. Conversely, digitalization opens opportunities for the DPS to enhance supervisory effectiveness through technologies such as RegTech and SupTech. This study recommends strengthening the digital competency of DPS human resources, harmonizing cross-country regulations, and developing a comprehensive digital Sharia governance framework.